Salamin, G., Kohán, Z., Dobozi, E. and Péti, M. eds.: Climate-Friendly Cities. A Handbook on the Tasks and Possibilities of European Cities in Relation toClimate Change - Kovács, Zoltán (Hungarian Geographical Bulletin, 2012)
-